Financial Analysis of AbbVie, Johnson & Johnson, and Pfizer in the Pharmaceutical Industry - Fei, Yixuan (Transactions on Economics, Business and Management Research, 2024)
Innovation and market instability characterize the pharmaceutical sector, offering a variety of investment prospects. The research undertakes an extensive economic review of three leading pharmaceutical companies: AbbVie, Johnson & Johnson, and Pfizer. This study utilizes financial models like Ratio Analysis and PEG ratios to identify which investor categories—Value Investors, Income Investors, and PEG Investors—are the most inclined to favor these firms. The study indicates a particular allure for Value Investors towards Johnson & Johnson, attributed to its robust market stance and steady expansion. Financial backers prefer AbbVie and Pfizer, with each providing greater dividend returns in line with strategies driven by income. PEG Investors, aiming to strike a balance between pricing and market growth, frequently opt for AbbVie due to its appealing price-to-income growth ratio. This study’s results offer crucial understanding for investors, empowering them to customize their tactics and enhance their portfolio by making enlightened choices in the pharmaceutical field.